Neuroprotective potential of the Amazonian fruits Euterpe oleracea Mart. and Paullinia cupana Kunth - Gabriel Nóbrega da Costa; Letícia Yoshitome Queiroz; Isaque Nilton dos Santos; Helena Iturvides Cimarosti (Brazilian Journal of Pharmaceutical Sciences, 2023)
Abstract Acai (Euterpe oleracea Mart.) and guarana (Paullinia cupana Kunth) are native species from the Amazon Forest that in folk medicine are used to treat several diseases due to their anti-inflammatory and antioxidant properties. This review brings together findings from different studies on the potential neuroprotective effects of acai and guarana, highlighting the importance of the conservation and sustainable exploitation of the Amazon Forest. A bibliographic survey in the PubMed database retrieved indexed articles written in English that focused on the effects of acai and guarana in in vitro and in vivo models of neurodegenerative diseases. In general, treatment with either acai or guarana decreased neuroinflammation, increased antioxidant responses, ameliorated depression, and protected cells from neurotoxicity mediated by aggregated proteins. The results from these studies suggest that flavonoids, anthocyanins, and carotenoids found in both acai and guarana have therapeutic potential not only for neurodegenerative diseases, but also for depressive disorders. In addition, acai and guarana show beneficial effects in slowing down the physiological aging process. However, toxicity and efficacy studies are still needed to guide the formulation of herbal medicines from acai and guarana.